Grix Palm Cleaning Sponge / Nur Solehah Samsudin - Samsudin, Nur Solehah (2020)
Invented by Otto Bayer in 1937, the first kitchen sponges are made from polyurethane foam. At first, these sponges were easily destroyed during dish washing due to their fragility but as the technology progressed, these sponges were designed to be more durable. Even though the porous nature of sponges makes them great for retaining water, it also makes them a natural breeding ground for microbes. Because they’re used to clean soiled surfaces and dishes, sponges inevitably retain food residue. That, combined with their warm and humid environments, makes sponges the ideal breeding ground for bacteria. In fact, every time you clean a dirty plate or surface, you’re transferring the bacteria from the plate or surface to the sponge. Thus, a better material of sponge is needed to reduce the possibility to grow the bacteria. Next, without we realized we have been spending a lot of time in doing the dish. The repetitive step to add soap and water to the sponge steal our time a lot. At first you need to open the liquid soap bottle cap and add some soap to the sponge surface. Then a dry sponge shall be ineffective for washing so you might run some water to it to make it damp. There are so many steps just for a simple task. Not to mention, those who soak their sponge in diluted soap water then once the soap turns cloudy, they must change the soap again to remove the rotten one. Both of our hands are occupied. It is a lot of energy needed just for a dish. From here, we could say the conventional method in doing the dish is time-consuming. It would be useful if there is a product that can save your energy as well as your time.